Suicide and suicide risk factors: A literature review - S.M. Masango; S.T. Rataemane; A.A. Motojesi (South African Family Practice)
Suicide can be defined as intentional self-inflicted death. It is a serious cause of mortality worldwide. Suicide is considered as a psychiatric emergency and the awareness of the seriousness of suicide in our society should not be overlooked. It is a significant cause of death worldwide. It accounts for about 30,000 deaths annually in the USA and more than 5,000 deaths annually in South Africa, and the prevalence of suicide in our society is on the increase. Etiological factors for suicide include social, psychological and physical factors. But suicide is multi-factorial in nature. This review focuses mainly on the associated risk factors for suicide: demographic factors, psychiatric disorders, terminal or chronic medical conditions, and recurrent unresolved psychological stressors.